Decision, rationality, Lean methodology - Iris Cortez, Estela; Morales, Patricia Alejandra; Bazanini, Roberto; Iris Cortez, Estela; Morales, Patricia Alejandra; Bazanini, Roberto; Administrador, Administrador (Corporación Universitaria Americana, 2023)
Every day people are faced with countless decisions to make, some of them are trivial and even seem to be of automatic execution derived from the inertia of routines, while others can become significant with important implications in their future. The way in which people make decisions has always been a topic of great interest for professionals from different disciplines, both medical and in studies of people in their individual and social behaviors. Decisionmaking in organizations emerged as an object of study in the last century, with research aimed at characterizing the decision-making process, its components and decisionmaking in organizations. As the research was deepened, one of the lines of study was to determine whether the decision making of businessmen was only rational, and the role that emotions and intuitions had in that sense. The objective of this paper is to reflect various theoretical contributions regarding biases in organizational decision making. This paper is predominantly descriptive in nature, the research was based on a qualitative approach strategy, which included the review of primary and secondary sources, for which an exhaustive review of national and international scientific production was carried out.